Linear polarization and directional distribution of gamma-rays from oriented172Lu - Nováková, D; Říkovská, J; Jankech, A; Ferencei, J; Pavlov, V; Finger, M (Kluwer Academic Publishers, 1983)
The gamma-ray linear polarization data in combination with the results of the directional distribution measurements were used to determine precise values of the multipole mixing ratios of the gamma-transitions in the172Yb nucleus. A detailed analysis of the deduced mixing ratios, supplemented by previous data, lends support to the following description of the two-quasiparticle excitations of192Yb (see also tab. 6): 2073 keV Kπ = (4+) {p 4041 ↓ + p 411 ↓} + {n 514↓ - n 521↓} 1663 keV Kπ = (3+) {n 514↓ - n 521↓} + {n 512↑ - n 521↓} 1172 keV Kπ = 3+ {n 512↑ + n 521↓} + {p404↓ - P 411↓} A supporting evidence has also been given to the spin-parity assignments of the 1640 keV (Iπ = 4-) and 1706 keV (Iπ = 5-) members of the Kπ = 4- band. © 1983 Academia, Publishing House of the Czechoslovak Academy of Sciences.